2023
DOI: 10.5194/bg-20-827-2023
|View full text |Cite
|
Sign up to set email alerts
|

Recently fixed carbon fuels microbial activity several meters below the soil surface

Abstract: Abstract. The deep soil, >1 m, harbors a substantial share of the global microbial biomass. Currently, it is not known whether microbial activity several meters below the surface is fueled by recently fixed carbon or by old carbon that persisted in soil for several hundred years. Understanding the carbon source of microbial activity in deep soil is important to identify the drivers of biotic processes in the critical zone. Therefore, we explored carbon cycling in soils in three climate zones (arid, mediterr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Under increased C inputs, the key challenge will be to ensure that newly added C is decomposed slowly, for example, due to mineral C adsorption. However, many studies have shown that most of the newly entered C, also at deeper depth, is decomposed relatively quickly and is typically not contributing to long‐term C storage (Balesdent et al., 2018; Scheibe et al., 2023; Stoner et al., 2021; Xiao et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Under increased C inputs, the key challenge will be to ensure that newly added C is decomposed slowly, for example, due to mineral C adsorption. However, many studies have shown that most of the newly entered C, also at deeper depth, is decomposed relatively quickly and is typically not contributing to long‐term C storage (Balesdent et al., 2018; Scheibe et al., 2023; Stoner et al., 2021; Xiao et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Because transit times are directly related to CS (Equations 21 and 22), we expect only tundra and boreal forest soils to store C in the subsoil at timescales relevant for climate change mitigation, that is, in the order of decades to centuries. In fact, previous studies have found that a large proportion of carbon used by microorganisms in the subsoil is recent and does not contribute to C stabilization in the subsoil (Balesdent et al., 2018; Scheibe et al., 2023). Therefore, we would expect lower values of CS for tropical forests, grasslands, and cropland soils in comparison with boreal forests and tundra soils.…”
Section: Empirical Evidence From Soil Profilesmentioning
confidence: 98%
“…A distinct property of most soils is the decrease of radiocarbon ( 14 C) activity with depth, indicating a higher average age of carbon since plant uptake from the atmosphere and a decrease in decomposition rates with depth (He et al., 2016; Heckman et al., 2022; Hicks Pries et al., 2023; Lawrence et al., 2020; Mathieu et al., 2015; Rumpel & Kögel‐Knabner, 2011; Scheibe et al., 2023). Potential factors responsible for this age gradient include (c.f.…”
Section: Processes Contributing To the Formation Of Soil Carbon Profilesmentioning
confidence: 99%
“…2). The likely reason for this is that both aridity and low temperatures lead to low decomposition rates 19,42 . Thus, at arid and cooler sites, SOC content is probably more strongly shaped by the decomposition rate than by the rate of organic carbon input to soil 43 , and consequently plant biomass and SOC are not correlated at these sites.…”
Section: Plant Biomass Soil Carbon and Climatementioning
confidence: 99%